Microwave power amplifier design for WiMAX subsciber station - Adi Wibowo, Nicholas (2009)
In this project, the design and development of power amplifier intended for wireless communication at 5.8GHz is carried out. Heterojunction bipolar transistor (HBT) is chosen as active device due to its excellent performance in high frequency region. The amplifier is built as switching amplifier to achieve high efficiency. At first, the amplifier is planned to be built as class E, however, the large output capacitance of active device prevents its effective operation. Therefore, a class F amplifier is considered for the design of this amplifier.